Assessment of the bending strength of mortise-tenon and dovetail joints in leg-and-rail construction using Klainedoxa gabonensis Pierre Ex Engl. and Entandrophragma cylindricum (Sprague) Sprague. Issue 4 (8th August 2017) - Boadu, Kwadwo Boakye; Antwi-Boasiako, Charles
ABSTRACT: Mortise-tenon joints for working chair construction fail under bending stresses. Dovetail joints could offer an alternative due to their resistance to bending. However, furniture joint strength depends on the design of the parts and appropriateness of the timber for the construction. Information on timber-joint design combination that would improve joint strength is lacking for most secondary timbers with prospects for joinery-making. This study assessed the bending strengths of two joint designs (dovetail and mortise-tenon) for leg-and-rail construction from Klainedoxa gabonensis (a secondary timber) and Entandrophragma cylindricum (popularly used for furniture). Dovetail joints were stronger than those of mortise-tenon. For both joints, the design with longer, wider and thicker tails and tenons [large-sized (Type LS)] was stronger than its counterpart [small-sized (Type SS)]. Joints manufactured from K . gabonensis were also stronger than those from E . cylindricum . Thus, K . gabonensis could be an appropriate material for joinery/furniture production. This would broaden the raw material base for the furniture sector. However, its working chairs designed with Type LS dovetail joints would resist bending forces better and ensure stronger furniture than mortise-tenon. To offset frequent furniture breakdown, this study provides designers with reliable information regarding joint strength from different timbers to guide selection.